2019
DOI: 10.1111/cns.13110
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive and monoclonal antibody treatment for myasthenia gravis: A network meta‐analysis

Abstract: Summary Background We intended to compare and rank all the immunotherapies including immunosuppressant agents or monoclonal antibodies for myasthenia gravis (MG). Methods A network meta‐analysis was performed to synthesize the direct evidence and indirect evidence. Quantitative MG score (QMGS) was defined as the primary outcome. The secondary outcomes included the glucocorticoid reduction and hazard ratios (HR) from the counts of adverse events (AEs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…Treatments with these agents are commonly initiated in conjunction with steroids so that they may be gradually tapered to a lower maintenance dose, which varies among individual patients 8 . A previous network meta‐analysis showed the efficacy and tolerability of the immunosuppressants were heterogeneous 9 …”
Section: Introductionmentioning
confidence: 99%
“…Treatments with these agents are commonly initiated in conjunction with steroids so that they may be gradually tapered to a lower maintenance dose, which varies among individual patients 8 . A previous network meta‐analysis showed the efficacy and tolerability of the immunosuppressants were heterogeneous 9 …”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that eculizumab, one of the latest generation treatment, was approved for the treatment of adults with AChR-associated gMG in the USA (183), AChR-associated refractory gMG in the EU (184) or patients with AChR-associated gMG whose symptoms are difficult to control with high-dose IVIg therapy or PE in Japan (185). One of a latest meta-analysis found that eculizumab is the most effective and tolerable therapeutic for refractory MG and tacrolimus is a beneficial therapy for MG extensively (186). Moreover, some new drugs are also under exploration which need further researches, such as efgartigimod (187).…”
Section: Mgmentioning
confidence: 99%
“…The complement system comprises more than 20 serum proteins, most of which are synthesized in the liver . These proteins are synthesized as inactive precursor proteins, which can be activated by appropriate stimuli . The activated forms of these proteins act as proteases and cleave other components successively in amplification pathways leading to an exponential generation of final effectors.…”
Section: Potential Targets Of Mabs and Their Applicationmentioning
confidence: 99%
“…Furthermore, blocking C5 can inhibit the formation of the MAC, dampening the destruction of NMJs and the subsequent production of proinflammatory factors . Molecules aimed at inhibiting complement cascade activation at the NMJ could represent an effective therapeutic approach of major interest .…”
Section: Potential Targets Of Mabs and Their Applicationmentioning
confidence: 99%
See 1 more Smart Citation